2022
DOI: 10.1002/lt.26510
|View full text |Cite
|
Sign up to set email alerts
|

Use of preprocurement biopsy in donation after circulatory death liver transplantation

Abstract: We perform routine preprocurement image‐guided percutaneous liver biopsies on potential donation after circulatory death (DCD) liver donors. The purpose of this study was to examine the impact of preprocurement liver biopsy on the use of livers from DCD donors. We retrospectively reviewed demographics, liver histology, and disposition of DCD liver donors within a single organ procurement organization (OPO) who underwent preprocurement liver biopsy from January 2000 through December 2019. A total of 212 potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Recently, an OPO reported their practice of premortem biopsies for DCD donors. 12 They found that premortem biopsy excluded 6.6% of DCD donors from liver donors. However, several points may warrant emphasis before premortem biopsies are considered for HCV-positive DCD donors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, an OPO reported their practice of premortem biopsies for DCD donors. 12 They found that premortem biopsy excluded 6.6% of DCD donors from liver donors. However, several points may warrant emphasis before premortem biopsies are considered for HCV-positive DCD donors.…”
Section: Discussionmentioning
confidence: 99%
“…Second, to use premortem biopsies, a long-standing collaborative relationship is required among the OPO, donor hospitals within donor service area, and transplant centers. 12 Therefore, with the more widespread sharing of DCD liver grafts outside of those transplant centers, the complexity of decision-making on whether liver grafts are warranted for biopsy and their allocation may increase. Finally, although the study suggests that premortem biopsy can help optimize human and equipment resources from an OPO standpoint, 12 premortem biopsy requires donor support specialists in working with families of potential donors, qualified local practitioners to perform the biopsy, and pathologists to evaluate it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Liver Transplantation , Bolognese et al [ 6 ] describe a novel method for potentially improving DCD liver utilization. This article details a single organ procurement organization (OPO) experience with pre‐recovery liver biopsy in potential DCD donors, and the central finding of the study is that the availability of biopsy data promoted improved utilization of DCD livers.…”
mentioning
confidence: 99%